Antifouling activity of bacterial extracts associated with soft coral and macroalgae from the Red Sea - Tunkal Rabab Ibrahim; Jamal Mamdoh T.; Abdulrahman Idris; Pugazhendi Arulazhagan; Satheesh Sathianeson (Oceanological and Hydrobiological Studies)
In marine environments where biofouling occurs and has an impact on the maritime economy and environment, compounds that inhibit the attachment, growth and survival of microorganisms in a biofilm complex as well as settlement of larvae are considered potential antifouling compounds. In this study, the extracellular metabolites from two surface-associated bacteria isolated from soft coral and macroalga were evaluated for antibiofilm and antisettlement activity. The bacteria were identified using 16S rRNA gene sequencing, and the culture supernatant extract of each strain was evaluated for antibiofilm activity. The compounds present in the extracts were analysed using GC-MS. The two bacterial strains were identified as Bacillus licheniformis MBR1 and Vibrio alginolyticus MBR4 for the isolates from soft coral and macroalgae, respectively. The extracts inhibited the growth of biofilm-forming bacteria, biofilm formation and barnacle larval settlement. The GC-MS analysis of the extract detected the presence of compounds such as tetrapentacontane, octadecanoic acid, 2,3-dihydroxypropyl ester, hexadecanoic acid, 2-hydroxy-1-(hydroxymethyl) ethyl ester and 17-pentatriacontene. The results of the study show that extracellular metabolites of the bacteria associated with marine organisms could be used as natural antifouling compounds to control biofouling.